Influence of pragmatism and scholasticism on contemporary education development - Eva Puspitasari (Inovasi Kurikulum, 2024)
The foundation of this study lies in the longstanding debate between practice-oriented, experiential educational approaches (pragmatism) and more traditional, theory-centered methods grounded in deductive logic (scholasticism). This research examines the influence of the philosophical streams of pragmatism and scholasticism on contemporary education. Adopting a qualitative approach, the study employs comparative literature analysis to evaluate the application of these philosophies within the modern educational framework. Findings reveal that pragmatism plays a pivotal role in shaping an educational system that is dynamic, adaptable, and responsive to contemporary societal needs, particularly by linking learning to real-life experiences. Conversely, scholasticism contributes significantly by preserving the value of education founded on deep theoretical comprehension and systematic logic. The synergy between these two philosophical approaches is posited to create a more balanced and holistic curriculum, blending practical and theoretical aspects essential for fostering student competencies in modern education. This research offers a new perspective on curriculum formulation by integrating the strengths of both approaches. AbstrakLatar belakang penelitian ini berakar dari perdebatan panjang antara pendekatan pendidikan yang berorientasi pada praktik dan pengalaman langsung (pragmatisme) dan pendekatan pendidikan yang lebih tradisional berbasis teori dan logika deduktif (scholatisisme). Penelitian ini bertujuan untuk menganalisis pengaruh dua aliran filsafat pragmatisme dan scholatisisme terhadap pendidikan kontemporer. Pendekatan penelitian ini bersifat kualitatif, mengadopsi analisis literatur dengan metode komparatif guna mengevaluasi implementasi kedua aliran filsafat dalam konteks sistem pendidikan kontemporer. Hasil penelitian menunjukkan bahwa penelitian ini menawarkan perspektif baru dalam perumusan kurikulum yang efektif dengan mengintegrasikan kekuatan dari kedua pendekatan. Pragmatisme berperan penting dalam membentuk sistem Pendidikan yang dinamis, fleksibel, dan relevan dengan kebutuhan masyarakat kontemporer, khususnya dalam menghubungkan pembelajaran dengan pengalaman sehari-hari. Di sisi lain, scholatisisme memberikan kontribusi besar dalam mempertahankan pentingnya Pendidikan yang berbasis pada pemahaman teori yang mendalam dan logika yang sistematis. Sinergi antara kedua aliran filsafat ini diyakini mampu menciptakan kurikulum pendidikan yang lebih seimbang dan holistik, memadukan aspek praktis dan teoretis yang esensial bagi pengembangan kemampuan peserta didik di era kontemporer.Kata Kunci: pragmatisme; scholatisisme; pendidikan kontemporer